New ideas about the structure and functions of national ecological network in the context of modern postnonclassical concepts - Kazakova, Tetiana (Human Geography Journal, 2016)
Today the idea of sustainable development has revealed severe signs of disability as evidenced by the fact that the global environmental problem is steadily worsening. All this makes to question the methodological guidelines which are incorporated into the content of the concept of national ecological networks. One of the main methodological mistakes implied in the development of the concept of ecological networks is bright biocentrism which led to their designing in some virtual space, completely detached from the real spatial organization of society. In fact, building a national ecological network as a spatial phenomenon may not be feasible without “inscribing” it in the specific area subject to certain models of socio-natural interaction. The nearest natural and anthropogenic landscape components approach the state of harmony not barrier but contact borders (in the form of strips, ecotones). Thus the best “contact” between a man and nature should promote exactly informative and ideological functions performed by technogenesis objects. Such theoretical approach provides a new tool for the formalization of relations between nature and society in the organization of the environmental work including formation of the ecological network. So trips to anthropogenically disturbed landscapes under the new concept of ecotourism should consider all possible demands of tourists and visual observation of different forms and results of anthropogenic impact on nature. Involvement of technogenesis facilities to eco-tourism and local history work in regions of old industrial development has another socio-geographical aspect. Technogenic tourism which may be a separate branch of ecotourism is largely designed to overcome deep contradictions in complex civilizational fault line of the Ukrainian history. In particular, regions such as Kryvbas can provide tourist product mainly involving objects of industrial origin and content. The use of postnonclassical approaches to formation of the national ecological network reveals new features that should carry out modern alternative tourism destinations.